Contraceptive Practices among the Eligible Couples from a Rural and an Urban Area of Karnataka - Niranjan V Gummaraj; Margaret Menzil; Bhaskar Kurre; Deepa LN; Anand D Meundi (Medsci Publications, 2018)
Background: Every fifth birth in the world is an Indian, and 50% of the Indian population are of reproductive age. Contraceptive use in India is very poor. There is still a large unmet need for con- traception and hence the present study was planned. Objective: To assess the couple protection rate (CPR) among the eligible couples. Methodology: A cross-sectional study was conducted among the 600 eligible couples in the urban and a rural area of Karnataka us- ing a semi structured questionnaire during October 2017 to March 2018. Results: The couple protection rate was 59.33% among the eligible couples and 40.67% did not use any family planning methods. The major family planning method used was tubectomy (42.63%), and very few used OCPs (4.5%). CPR was highest among the couples who completed greater than 2 years of married life (60.76%) and who had 2 or more children (67.64%). All (100%) professional graduates used contraceptive methods while it was least (31.2%) among illiterates. Conclusion: The number of eligible couples still not using the fam- ily planning methods was 40.67%. Hence there is a need to educate and motivate the eligible couples to improve family planning ser- vices, highlighting the importance of small family.